Point prevalence survey of antibiotics use among hospitalised neonates and children in Saudi Arabia: findings and implications - Hind M. Alosaimi; Mohammed K. Alshammari; Mohammad M. Fetyani; Maha S. Allehidan; Tahani J. Almalki; Khansa H. Hussain; Haifaa H. Hussain; Mohammed D. Althobaiti; Abrar S. Alharbi; Atheer A. Alharthi; Amosha A. Al-shammari; Zainab A. Al Jamea; et al. (Journal of Pharmaceutical Policy and Practice, 2024)
Background Neonates and children are more susceptible to a variety of infections, leading to frequent antibiotic prescriptions. However, the inappropriate use of antibiotics leads to antibiotic resistance and higher mortality rates. Therefore, this study aimed to determine the prevalence of antibiotic use, and current antibiotic prescribing practices among neonates and children admitted in the selected hospitals of Saudi Arabia.Methods A cross-sectional study was conducted from September to November 2023 to assess the prevalence of antibiotic use, and the current antibiotic prescribing practices across six hospitals of Saudi Arabia.Results The study included 499 children and neonates, with 94.6% receiving antibiotic prescriptions. The most frequently prescribed antibiotic class was third-generation cephalosporin (31.5%), with ceftriaxone being the most commonly prescribed antibiotic (15%). The majority of patients were prescribed one antibiotic (81.4%), and the intravenous route (96.4%) was the primary route for administration. The majority of patients were prescribed antibiotics empirically (69.7%), and community-acquired infections (64.2%) were the most common type of infection for antibiotic prescription. Similarly, sepsis (39.2%) was the most common indication for antibiotics, and the majority of prescribed antibiotics (61.7%) belonged to the ‘Watch’ category as per WHO AWaRe classification.Conclusion Our study revealed excessive antibiotic consumption in neonates and children, therefore quality improvement programmes including antimicrobial stewardship programmes are urgently needed to address ongoing issues.